Androgen generation in adipose tissue in women with simple obesity--a site-specific role for 17beta-hydroxysteroid dehydrogenase type 5. - Quinkler, M; Sinha, B; Tomlinson, J; Bujalska, I; Stewart, P; Arlt, W (2004)
Women with polycystic ovary syndrome (PCOS) have high circulating androgens, thought to originate from ovaries and adrenals, and frequently suffer from the metabolic syndrome including obesity. However, serum androgens are positively associated with body mass index (BMI) not only in PCOS, but also in simple obesity, suggesting androgen synthesis within adipose tissue. Thus we investigated androgen generation in human adipose tissue, including expression of 17beta-hydroxysteroid dehydrogenase (17beta-HSD) isozymes, important regulators of sex steroid metabolism. Paired omental and subcutaneous fat biopsies were obtained from 27 healthy women undergoing elective abdominal surgery (age range 30-50 years; BMI 19.7-39.2 kg/m(2)). Enzymatic activity assays in preadipocyte proliferation cultures revealed effcient conversion of androstenedione to testosterone in both subcutaneous and omental fat. RT-PCR of whole fat and preadipocytes of subcutaneous and omental origin showed expression of 17beta-HSD types 4 and 5, but no relevant expression of 17beta-HSD types 1, 2, or 3. Microarray analysis confirmed this expression pattern (17beta-HSD5>17beta-HSD4) and suggested a higher expression of 17beta-HSD5 in subcutaneous fat. Accordingly, quantitative real-time RT-PCR showed significantly higher expression of 17beta-HSD5 in subcutaneous compared with omental fat (P<0.05). 17beta-HSD5 expression in subcutaneous, but not omental, whole fat correlated significantly with BMI (r=0.51, P<0.05). In keeping with these findings, 17beta-HSD5 expression in subcutaneous fat biopsies from six women taking part in a weight loss study decreased significantly with weight loss (P<0.05). A role for 17beta-HSD5 in adipocyte differentiation was further supported by the observed increase in 17beta-HSD5 expression upon differentiation of stromal preadipocytes to mature adipocytes (n=5; P<0.005), which again was higher in cells of subcutaneous origin. Functional activity of 17beta-HSD5 also significantly increased with differentiation, revealing a net gain in androgen activation (androstenedione to testosterone) in subcutaneous cultures, contrasting with a net gain in androgen inactivation (testosterone to androstenedione) in omental cultures. Thus, human adipose tissue is capable of active androgen synthesis catalysed by 17beta-HSD5, and increased expression in obesity may contribute to circulating androgen excess.